The Influence Of Employee Performance Competence On The Indonesian Coast Guard Ships - Makmun, Moh. Syukron; Widhapahlevi Putri, Rechtdina; Firman; Wahyuning Dewi, Triana; Umar Fauzi, Muhammad; Wardana, Ali (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to determine (1) the influence of intellectual competence, emotional competence and social competence of employees on employee performance and, (2) the most dominant factors influencing employee performance on the State Ships of the Indonesian Maritime Security Agency or Indonesian Coast Guard (KN Bakamla RI) in 2023. There are the diverse competencies possessed by Bakamla employees who serve on the Republic of Indonesia’s KN Bakamla cause less than optimal organizational performance so that an effort is needed to fill this gap. This research is mix method research, namely a combination of quantitative methods and qualitative methods. Data was collected using the methods (1) interviews, (2) documentation, and (3) questionnaires. Next, the data was processed and analyzed using multiple linear regression analysis, SPSS version 22 program and descriptive analysis. The results of the research show that employee competency influences employee performance at KN Bakamla RI, both partially and simultaneously. Partially, intellectual competence has a partial influence of 76.6% on performance, then emotional competence has a partial influence of 58.3% on performance, and social competence has a partial influence of 62.8% on performance. Simultaneously, intellectual competence, emotional competence, and social competence have a large influence on 62.3% of employee performance. There needs to be regular competency development so that employees can develop their competencies to further improve performance. This research was conducted in April-May 2024.